High prevalence of circulating autoantibodies against thyroid hormones in vitiligo and correlation with clinical and historical parameters of patients. (1st October 2014) - Colucci, R.; Lotti, F.; Dragoni, F.; Arunachalam, M.; Lotti, T.; Benvenga, S.; Moretti, S.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Vitiligo is strongly associated with autoimmune thyroid disorders. Autoantibodies against thyroid hormones (THAbs) have a very low prevalence in the general population and are increased in thyroid and extrathyroid autoimmune diseases. What does this study add? For the first time, THAbs against triiodothyronine (T3‐Ab) and thyroxine (T4‐Ab) have been detected in a group of patients with vitiligo. T3‐Ab and T4‐Ab were associated with some clinical and historical parameters of vitiligo.